Experiential Pedagogies for Cultivating Entrepreneurial Mindsets: Action Design Learning as Tailored Framework - Futonge Nzembayie, Kisito; Talay, Isilay (My University, 2024)
Despite the recent recognition of experiential learning as an effective pedagogy for cultivating entrepreneurial mindsets, it still lacks a robust and tailored conceptual foundation primed for adoption in entrepreneurship education (EE). Addressing this deficit, this research integrates action learning and design learning to propose Action Design Learning (ADL) as a bespoke and adaptable framework for experiential learning in EE. ADL fosters entrepreneurial mindsets by placing first- and second-person learning at the core of pedagogy, using emergent entrepreneurial artifacts as focusing devices. Through longitudinal insider action research, the framework is abductively evaluated across two cases in Irish universities, culminating in a functional adaptation primed for adoption. The study reveals that ADL provides a robust conceptual foundation that educators can readily apply in designing and delivering high-impact curricula that foster metacognitive abilities deemed foundational to an entrepreneurial mindset. Consequently, this study contributes to the experiential learning discourse by offering a theoretically grounded pedagogy that overcomes skepticism about the efficacy of this approach in promoting high-impact EE.
PUBLISHED
Keywords: Entrepreneurship education, action design learning, entrepreneurial mindset; Identities in Transformation; Entrepreneurship; Innovation; Management Education